Learning through Collaborative Data Projects: Engaging Students and Building Rapport - Matthew T. Pietryka; Rebecca A. Glazier (MDPI AG, 2022)
Many instructors strive to make students more active participants in their own learning. Yet recommended methods for this purpose, such as project-based learning or providing personalized feedback, are impractical in larger classes or virtual classrooms. To overcome these barriers, we designed a series of collaborative data projects to engage students even in large, online classes. Our goal is to describe and evaluate the efficacy of these projects. The projects offer two major benefits. First, the collective nature of the projects helps students to see how their individual efforts contribute to a larger outcome. Second, the instructor can aggregate the student input and provide personalized feedback using free software, thus, reducing the grading and contact burden while simultaneously building rapport. We examine survey data from about 120 students from four classes during Spring and Fall 2021. The students report that they tend to learn more and find these collaborative assignments more enjoyable compared to a typical college assignment. They also report that receiving individualized feedback increases their interest in the material and makes them feel like the instructor is invested in their learning. We include assignment examples and programming recommendations to help instructors adapt this collaborative engagement method for their own courses.